2012
DOI: 10.7314/apjcp.2012.13.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Curative and Side Effects of Chemoradiotherapy among Xinjiang Han, Uigur and Kazakh Esophageal Carcinoma Patients

Abstract: Objective: This study aimed to explore the differences in the curative and side effects of chemoradiotherapy on esophageal cancer (EC) among Xinjiang Han, Uigur and Kazakh patients. Methods: 170 patients with IIA stage-IV of esophageal squamous cell carcinoma were analyzed retrospectively. Based on different nationalities, they were divided into the Han, Uigur and Kazakh groups. The 1-, 2-and 3-year survival rates, incidence of the side effects (including hematological toxicities, radioactive esophagitis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Based on the results of clinical efficacy and preliminary of experimental studies, and at the same time when we retrospectively analyzed 170 cases of ESCC patients from different ethnic groups and compared the efficacy and side effects of different ethnic groups during the clinical observation, we found that the short-term efficacy of esophageal cancer chemotherapy of Han, Uyghur, and Kazakh patients in Xinjiang were similar, but the long-term survivals were different: the Han patients were better than Uyghur and Kazakh. However, Uyghur and Kazakh patients’ side effects were relatively lighter, and they were better tolerated [ 8 ]. And we simultaneously applied ELISA and immunohistochemistry to detect the expression levels of VEGF, EGFR, ES, and HER-2 and the NF-kBp in serum and tissue of Han, Kazakh, and Uyghur ESCC patients, the results indicated that there were ethnic differences in serum tumor marker levels of Han, Uyghur, and Kazakh ESCC patients in Xinjiang [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of clinical efficacy and preliminary of experimental studies, and at the same time when we retrospectively analyzed 170 cases of ESCC patients from different ethnic groups and compared the efficacy and side effects of different ethnic groups during the clinical observation, we found that the short-term efficacy of esophageal cancer chemotherapy of Han, Uyghur, and Kazakh patients in Xinjiang were similar, but the long-term survivals were different: the Han patients were better than Uyghur and Kazakh. However, Uyghur and Kazakh patients’ side effects were relatively lighter, and they were better tolerated [ 8 ]. And we simultaneously applied ELISA and immunohistochemistry to detect the expression levels of VEGF, EGFR, ES, and HER-2 and the NF-kBp in serum and tissue of Han, Kazakh, and Uyghur ESCC patients, the results indicated that there were ethnic differences in serum tumor marker levels of Han, Uyghur, and Kazakh ESCC patients in Xinjiang [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of esophageal SCC pointed out that the tumors in Uygur patients showed more resistance to radiotherapy and chemotherapy than Han patients, and radiotherapy/chemotherapy resulted in longer survival of Han patients. [ 60 ] We can speculate that the in vivo condition of the Uygur patient confers a more suitable microenvironment for the occurrence, survival, and proliferation of SCCs. In addition, Uygur children in Xinjiang have higher obesity frequency than other Chinese ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Although Zhang et al explored the differences in the curative and side effects of chemoradiotherapy on EC among Xinjiang Han, Uygur and Kazakh patients. But their sample size was not large enough, totaling 170 [11]. A piece of study has reported that 5-year OS of ESCC patients undergoing radiotherapy was about10% [8].…”
Section: Introductionmentioning
confidence: 99%